1998
DOI: 10.1086/301715
|View full text |Cite
|
Sign up to set email alerts
|

Nearby Stop Codons in Exons of the Neurofibromatosis Type 1 Gene Are Disparate Splice Effectors

Abstract: Stop mutations are known to disrupt gene function in different ways. They both give rise to truncated polypeptides because of the premature-termination codons (PTCs) and frequently affect the metabolism of the corresponding mRNAs. The analysis of neurofibromin transcripts from different neurofibromatosis type 1 (NF1) patients revealed the skipping of exons containing PTCs. The phenomenon of exon skipping induced by nonsense mutations has been described for other disease genes, including the CFTR (cystic fibros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
57
3
2

Year Published

1999
1999
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(64 citation statements)
references
References 46 publications
2
57
3
2
Order By: Relevance
“…It appears that an alternative mechanism may alter the interaction between an exonic splice enhancer and mRNA splicing factors of the CALD1 via a signaling pathway modifying the splicing apparatus. 2,47,48 The regulation of the transcriptional activation of CALD1 splicing variants could have far-reaching epigenetic effects on the development of molecular targeted anti-angiogenic therapies.…”
Section: Discussionmentioning
confidence: 99%
“…It appears that an alternative mechanism may alter the interaction between an exonic splice enhancer and mRNA splicing factors of the CALD1 via a signaling pathway modifying the splicing apparatus. 2,47,48 The regulation of the transcriptional activation of CALD1 splicing variants could have far-reaching epigenetic effects on the development of molecular targeted anti-angiogenic therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Among the mutations characterized, three were located in exon 7. One of the three stop mutations has previously been described (Hoffmeyer et al, 1998) and shown to be associated with exon skipping. The remaining two mutations in exon 7 were novel.…”
Section: Introductionmentioning
confidence: 99%
“…The protein truncation test (PTT) provides the advantage over other methods to screen the entire coding region of the NF1 gene for nonsense or frameshift mutations which represent about 80% of the characterised mutations in the NF1 gene so far (Shen et al, 1996). This technique also allows the detection of aberrantly spliced transcripts (Heim et al, 1995;Messiaen et al, 1997;Hoffmeyer et al, 1998;Park and Pivnick, 1998). Usually, aberrant transcripts are indicative for mutations in splice or branching sites of exons.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…exon or multiexon deletions/duplications) (Wimmer et al, 2006), and the remaining patients present intragenic minor lesions including single nucleotide changes and small deletions and insertions. Although the existence of several recurrent NF1 mutations has been reported (Hoffmeyer et al, 1998;Ars et al, 2000Ars et al, , 2003Fahsold et al, 2000;Messiaen et al, 2000), each one accounts for only a small proportion of patients, which suggests that complete analysis of the entire coding region should be a mandatory procedure in any screening strategy. Exhaustive double DNA/RNA studies in early 2000 revealed that a significant proportion of mutations affected the correct splicing of the gene, even in cases where canonical splicing sequences were not affected (Ars et al, 2000(Ars et al, , 2003Fahsold et al, 2000;Messiaen, et al, 2000).…”
Section: Introductionmentioning
confidence: 99%